VD_FINDINFO HC / 2015 / 521 vom 1. Juni 2015 - VD Tribunal cantonal (2015)
CERTIFICAT D'HÉRITIER, RÉPUDIATIONDROIT SUCCESSORAL, DÉCISION D'IRRECEVABILITÉ | 566 al. 1 CC, 566 CC, 321 al. 1 CPC (CH), 321 al. 2 CPC (CH), 321 CPC (CH), 108 al. 1 CDPJ, 133 CDPJ